Determination of physical and mechanical properties as maturity indices for mango variety Nam Dokmai - Phanida Busaparoek; Athapol Noomhorm; Jindal, Vinod Kumar; Ilangantileke, S.G.; Vincent, J.C.; Rajamangala Institute of Technology (Bangkok : Asian Institute of Technology, 1993)
A testing unit for nondestructive evaluation of quality of "Nam Dokmai" mango using a mechanical exciter and piezoelectric film transducer for determination of mechanical properties, was developed. Mechanical properties, total soluble solids and physical characteristics of mango at different maturity stages from eight to fifteen weeks after fruit set, were measured. The correlations between mechanical properties, total soluble solids, physical characteristics and maturity were investigated. It was found that physical characteristics such as weight, volume, specific gravity, width, thickness and total soluble solids of mango increased with maturity. Mechanical properties using punch test such as rupture force and slope of force-deformation curve decreased with maturity. For mechanical properties using nondestructive test, shock wave propagation velocity, magnitude of maximum peak and magnitude of a 200 Hz component in the frequency spectrum increased with maturity, while attenuation coefficient decreased with maturity. The correlation between mechanical properties, total soluble solids and physical characteristics were also determined. The parameters, including shock wave propagation velocity, magnitude of maximum p·eak and magnitude of 200 Hz component have been shown to identify the maturity stage of "Nam Dokmai" mango. However magnitude of positive maximum peak was found to be the best indication of maturity.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering.
Keywords: Mango